2019
DOI: 10.1017/jns.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implementing school meals compared with packed lunches on quality of dietary intake among children aged 7–13 years

Abstract: Strategies are needed to improve the dietary habits of children. The aim of the present study was to evaluate the effect of implementing a school food programme on the dietary quality of lunches consumed by school children aged 7–13 years compared with packed lunches brought from home. A secondary objective was to investigate if a possible effect would differ between the younger children and the older. A quasi-experimental study design with four intervention schools and four matched control schools was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
1
12
0
1
Order By: Relevance
“…This suggests that interventions such as free school meals offered as they were in our project might result in improved educational-, employment-, and health outcomes later in life. Findings from this present study are consistent with previous research, showing great potential of free school meals ( 4 , 5 , 22 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that interventions such as free school meals offered as they were in our project might result in improved educational-, employment-, and health outcomes later in life. Findings from this present study are consistent with previous research, showing great potential of free school meals ( 4 , 5 , 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Evidence suggests that providing free school meals can contribute to an overall healthier diet, especially for students living in socioeconomically disadvantaged households ( 4 , 5 , 21 ). Free school meals have been linked to increased fruit and vegetable intake, and improved attention and energy in students.…”
Section: Popular Scientific Summarymentioning
confidence: 99%
“…In the OPUS School Meal study, which provided free lunches to all 3rd and 4th grade students in nine schools in Demark for three months (and the students ate packed lunches from home for three months) found significant improvements in students’ diets, including 16% higher vegetable intakes ( p < 0.0001) and 48% higher fish intakes ( p < 0.0001), as well as 30% lower intakes of saturated fats ( p < 0.0001) [ 82 ]. Lastly, a similar study conducted in Denmark among four schools that provided free school lunches for two months (compared with control schools with lunches packed from home only) also found that free meals were associated with improved dietary quality, including reductions in saturated fat and snacks and increases in vegetables and fish [ 83 ]. When the school meals were no longer provided at no cost after the two-month period, participation in school lunch became limited and there were no longer improvements in dietary quality observed.…”
Section: Resultsmentioning
confidence: 99%
“…School closures have led to distance-learning and home-schooling-not to mention challenges to food distribution: school is the place where many children around the globe get a consistent daily caloric intake. School-based nutrition is a reality in both developing and developed countries [7][8][9]. Parents are experiencing increased pressure to work from home, to keep jobs and businesses running, as well as to support, educate and comfort their children at the same time.…”
Section: Open Accessmentioning
confidence: 99%